2002
DOI: 10.1021/bi0117605
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Catalysis by the Ketoreductase Activity in the First Extension Module of the Erythromycin Polyketide Synthase

Abstract: Multiple ketoreductase activities play a crucial role in establishing the stereochemistry of the products of modular polyketide synthases (PKSs), but there has been little systematic scrutiny of catalysis by individual ketoreductases. To allow this, a diketide synthase, consisting of the loading module, first extension module, and the chain-terminating thioesterase of the erythromycin-producing PKS of Saccharopolyspora erythraea, has been expressed and purified. The DNA encoding the ketoreductase-1 domain in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 36 publications
8
56
2
Order By: Relevance
“…These results confirm previous indications that substantial [11] or total [21,29] deletion of a KR domain within a modular PKS does not inactivate polyketide chain synthesis, and are consistent with the proposal that KR domains do not contribute to the dimeric core in PKS multienzymes. [5,6,8] Fermentation of recombinant S. erythraea (pJLK29), housing a DEBS 1-TE variant in which the reductive loop of module 10 of RAPS (KR and DH domains) had been inserted in the linker gave as predicted the open chain triketides 6 a and 6 b (analysed as their methyl esters).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm previous indications that substantial [11] or total [21,29] deletion of a KR domain within a modular PKS does not inactivate polyketide chain synthesis, and are consistent with the proposal that KR domains do not contribute to the dimeric core in PKS multienzymes. [5,6,8] Fermentation of recombinant S. erythraea (pJLK29), housing a DEBS 1-TE variant in which the reductive loop of module 10 of RAPS (KR and DH domains) had been inserted in the linker gave as predicted the open chain triketides 6 a and 6 b (analysed as their methyl esters).…”
supporting
confidence: 91%
“…[25] There is an additional obligatory epimerisation step in module 1, after condensation, to produce the substrate for ketoreduction. [26][27][28][29] The stereochemical outcome therefore essentially depends on the interplay between the properties of individual KS and KR domains. In any chimaeric extension module that generates a methyl centre at C-2 and a hydroxy centre at C-3, if the product of condensation is exactly that stereoisomer of the 2-methyl-3-ketoacyl thioester intermediate which matches the normal preference of the incoming KR, then the heterologous KR often imposes the stereochemical course of its normal reaction on the new substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction intensities were integrated, reduced, and scaled using the program HKL2000 (22). The crystal space groups for all ternary complexes are P3 2 21, and cell dimensions varied by 1-2 Å. A summary of the crystallographic data is shown in Table 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous studies with FAS (20,37) and type I polyketide KRs (21) have shown that monocyclic ketones (such as 12-16) of various length and substitution patterns can be used as in vitro substrates for these KRs. However, in the case of actKR, we could not detect enzyme activity for any linear or monocyclic ketones, as well as acetoacetyl-CoA or acetoacetyl-ACP.…”
Section: In Vitro Assay Of Actkr: a Significant Preference For Bicyclmentioning
confidence: 99%
“…Recombinant DEBS KR1 reduces racemic 2-methyl-3-ketopentanoyl-SNAc exclusively to a syn-(2S,3R)-2-methyl-3-hydroxy diketide (NDK-SNAc), thereby demonstrating that this reductase is completely specific not only for reduction on the re-face of the ketone carbonyl but also for the natural L-configuration of the adjacent 2-methyl group, consistent with the overall stereospecificity of DEBS module 1 (59,60 (Fig. 4a) (61,62).…”
Section: Stereochemistry Of Kr-catalyzed 3-ketoacyl-acp Reductionsmentioning
confidence: 54%